Persepsi Kemudahan, Kegunaan, Keamanan dan Kerahasiaan Sistem Pelaporan Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Jhon , Susan Beby; Natalia, Erni Yanti (CV. ITTC INDONESIA, 2025)
The development of digital technology has had a significant impact on various aspects of life, including government administrative systems, particularly in the field of taxation. Digitalization facilitates data management and provides faster and more accurate access to information through the internet. In the context of taxation, digitalization offers convenience for taxpayers in fulfilling their tax obligations efficiently and transparently. One form of innovation introduced by the government is the implementation of the electronic tax reporting system (e-Filing), aimed at increasing service efficiency and tax compliance. However, the level of compliance among Individual Taxpayers (WPOP) in using the e-Filing system remains relatively low.This study aims to analyze the influence of perceived ease of use, usefulness, security, and confidentiality on WPOP compliance at the Batam Selatan Tax Office (KPP Pratama). The research used a purposive sampling method, involving a total of 100 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis.The results of the study indicate that all independent variables—perceived ease of use, usefulness, security, and confidentiality—have significant effects on WPOP compliance. Perceived ease of use has a significance value of 0.034 < 0.05, usefulness 0.000 < 0.05, security 0.002 < 0.05, and confidentiality 0.011 < 0.05. Simultaneously, these four variables also have a significant effect on taxpayer compliance, indicating the importance of these factors in enhancing individual taxpayer compliance through the e-Filing system.Keywords: Perceived Ease of Use, Perceived Usefulness, Perceived Security, Perceived Privacy, Taxpayer Compliance